The Micro-level Price Response to Monetary Policy - Almut Balleer; Peter Zorn (ZBW - Leibniz Information Centre for Economics, 2020)
We estimate the effects of monetary policy on price-setting behavior in administrative micro data underlying the German producer price index. After expansionary monetary policy, the increase in the frequency of price change is economically small, the average absolute size across all price changes falls, and the aggregate price level hardly adjusts as a result. These estimates imply a strong degree of monetary non-neutrality because they rule out quantitative structural models that generate small and transient effects of monetary policy through selection on large price adjustments.
Keywords: E30; E31; E32; E52; 330; price setting; extensive margin; intensive margin; monetary policy; local projections; menu cost